Rebound adenotonsillar and thymic uptake of 18F-FDG in paediatric patients with lymphoma. Issue 133 (December 2020) - Hu, Ying-Ying; Zhao, Yu-Mo; Zhang, Xu; Zhou, Chao; Li, Yuan-Hua; Long, Wen; Fan, Wei
Highlights: In paediatric lymphoma patients, adenotonsillar and thymic FDG uptake rebounded during months of disease-free follow-up. Rebound FDG uptake was more commonly seen than the morphological rebound enlargement reported in the literature. The peak measured SUV of the rebound FDG uptake was sometimes alarmingly high. Benign but evident rebound FDG uptake commonly occur during post-treatment surveillance warranting correct interpretation. Abstract: Purpose: To evaluate the treatment-dependent changes in FDG uptake in the adenoid, palatine tonsils, and thymus in paediatric patients with lymphoma. Methods: Eight hundred PET/CT scans of 212 paediatric patients between 2007 and 2019 (mean age, 11.9 years; median follow-up, 26.2 months) were retrospectively reviewed for discernible FDG uptake in the adenoid (A+), palatine tonsils (P+), and thymus (T+). The distribution of metabolic activity in the interested lymphoid organs was examined. Statistical analysis was performed using SPSS packages. Results: There were 513 (64 %) A + scans, 548 (69 %) P + scans, 270 (48 %) T + scans identified. The percentage of A + was 88 % at baseline, decreased to 48 % at the end of treatment, and then rebounded to 73 % during follow up; P + went from 79 % to 45 % then to 82 %; and for T + was 75 %, 21 %, 72 %. SUVmax was significantly higher (P < 0.001) in scans performed during follow-up than that of the baseline (A + 7.0 ± 3.5 vs. 5.8 ± 2.5; P + 9.4 ± 3.5 vs. 8.2 ± 2.8; T + 4.0 ± 1.4 vs. 3.4 ± 1.1). A + and P + peaked between 6–12 months of follow-up with a SUVmax of 7.6 ± 3.2, 10.6 ± 3.2, accordingly; T + peaked within 3–12 months with a SUVmax of 4.4 ± 1.4. Despite that A + and T + were more commonly seen in younger patients at any given study time, evident uptake rebound persisted in patients aged ≥16. Conclusions: In paediatric patients with lymphoma, evident and benign rebound adenotonsillar and thymic 18 F-FDG uptake commonly occur during post-treatment surveillance.